2021
DOI: 10.1186/s12884-021-04197-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kinesio taping on low back pain during pregnancy: a systematic review and meta-analysis

Abstract: Background Low back pain during pregnancy affects the normal daily activities of pregnant women to a certain extent. Current studies have shown that Kinesio Taping (KT) may be a treatment for low back pain during pregnancy, but there is still a lack of key evidence. The purpose of this study is to evaluate the efficacy and safety of KT in the treatment of low back pain during pregnancy. Methods PubMed, Web of Science, The Cochrane Library, Scopus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
2
8
0
2
Order By: Relevance
“…These results are in agreement with a metaanalysis (Xue et al, 2021) showing that kinesiotaping, either alone or in combination with other common therapies, results in greater pain relief and functional improvement in pregnant women with low back pain. Another study stated that for patients with low back pain during pregnancy, progressive muscle relaxation therapy and kinesiotaping can help reduce lower back pain (Chen et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with a metaanalysis (Xue et al, 2021) showing that kinesiotaping, either alone or in combination with other common therapies, results in greater pain relief and functional improvement in pregnant women with low back pain. Another study stated that for patients with low back pain during pregnancy, progressive muscle relaxation therapy and kinesiotaping can help reduce lower back pain (Chen et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Musculoskeletal and usually pose a risk of low back pain (Gharaibeh et al, 2018). In a study (Xue et al, 2021) it has been reported that women who suffer from severe low back pain during pregnancy have a very high risk of experiencing recurrent pain during subsequent pregnancies and later in life, therefore the problem of low back pain during pregnancy cannot be resolved. ignored…”
Section: Introductionmentioning
confidence: 99%
“…There was very limited evidence in this systematic review that kinesiotaping plus paracetamol is better than paracetamol alone 63 ; and that kinesiotaping is not better than placebo in reducing pain intensity and disability amongst pregnant women with low back pain 64 . This contradicts consistent evidence suggesting that kinesiotaping is more effective than placebo and/or passive or active interventions such as exercise in reducing pain intensity and/or disability amongst pregnant women with low back pain 109,110 . This contradicting nding could be because the trial included in this systematic review 64 which was not included in the other systematic reviews may have been underpowered to detect any statistical signi cance.…”
Section: Discussionmentioning
confidence: 74%
“…We will apply the Grading of Recommendations Assessment, Development and Evaluation (GRADE) method to evaluate the level of confidence in regards to outcomes. [18,19] Two independent reviewers will conduct the assessment. In most cases, disagreements were resolved by discussion between the 2 researchers.…”
Section: Search Strategymentioning
confidence: 99%